Propionic acid mediates the renoprotective effects of fecal microbiota transplantation against ischemia–reperfusion injury via upregulating GPR43 - Yu, Jingxuan; Liu, Zhenyu; Wang, Yan; Zhou, Yu; Liu, Wei; Wang, Tao; Xie, Qiubo; Tian, Hongzhe; Xu, Yalong; Wang, Min; Zhao, Fuhan; Wang, Lin; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionKidney ischemia–reperfusion injury (IRI) is a major cause of acute kidney injury (AKI), characterized by aggravated inflammation and apoptosis following reperfusion. This study aimed to investigate the protective effects and mechanisms of fecal microbiota transplantation (FMT) in a rat model of kidney IRI.MethodsSprague–Dawley rats(SDRs) subjected to 45 minutes of bilateral renal ischemia followed by reperfusion were prophylactically treated with FMT derived from guinea pigs or supplemented with propionic acid. Renal function, histopathology, inflammatory markers, apoptosis, proliferation, and gut microbiota composition were systematically evaluated.ResultsThe results demonstrated that FMT attenuated kidney IRI by remodeling the gut microbiota to enhance propionic acid production, which subsequently modulated inflammation and apoptosis via GPR43 signaling.ConclusionsThese findings provide novel insights into microbiota-targeted therapeutic strategies for kidney IRI and highlight propionic acid as a potential therapeutic agent.